Shape optimization of an elliptic cylinder located in adiabatic flows. Issue 1 (1st January 2018) - Mochizuki, Yuta; Kawahara, Mutsuto
Abstract: The purpose of this paper is to present a shape optimization method for the drag force reduction problem of an elliptic cylinder located in fluid flows. The fluid is assumed to be in an adiabatic state. The conservation equations of mass and momentum are used with the density and momentum employed as field variables. For the discretization, the finite element method is applied using SUPG stabilization based on a linear interpolation function is used. The performance function consists of the square sum of the drag forces, integrated between the starting and final times. The coordinates of the surface of the cylinder are updated to obtain the minimal performance function. For this minimization procedure, we employ the weighted gradient method using the solution of the adjoint equation. A numerical computation is executed to demonstrate that the proposed method is effective for the drag reduction problem.